If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/5(g)=-6
We move all terms to the left:
3/5(g)-(-6)=0
Domain of the equation: 5g!=0We add all the numbers together, and all the variables
g!=0/5
g!=0
g∈R
3/5g+6=0
We multiply all the terms by the denominator
6*5g+3=0
Wy multiply elements
30g+3=0
We move all terms containing g to the left, all other terms to the right
30g=-3
g=-3/30
g=-1/10
| 5=k5 | | 12z–(4z+6)=82 | | 5x=1/2(16+6x) | | x=1/3=2-3x/2=-1 | | 7x-3-2x=5x-3 | | 4+4m=9+2m | | k/7=-9 | | 4+5m=6+2m | | 5.2(x-4.25)=-20.8 | | 3(x-2)=4x-3-x | | -25+u=344 | | -27=-6(2+4x)-6x | | -10y-4=6 | | 125x+25=25(5x+1) | | 7m-12=5 | | 4+1/5x+36=10 | | 3/4=w+7/8 | | -2(4x+3)+3(6x+1)=37 | | -2-6x=8 | | 258=-8(4b-6)-3b | | 56x2x=60 | | 50(t)=-16t^2+63t+4 | | -2-4x=7 | | 9p+2=3 | | 4(d+4)=2(2d-3) | | 4b=-53 | | 2m-1=5m+8 | | 2+5w=32 | | 5r-(2r+8)=10 | | -2(×+3)=2x-6 | | 6m+5-5m=10-4m+20 | | 6p+5=11 |